Strange Case of Dr Jekyll and Mr Hyde - Rob Lloyd Jones (ENGLAND USBORNE PUBLISHING, 2010)
A new title in Young Reading Series Three, based on the classic spine-chiller by Robert Louis Stevenson. Aimed at children whose reading ability and confidence allows them to tackle longer and more complex stories. Age 7+ The classic tale by Robert Louis Stevenson retold for children ready to tackle longer and more complex stories. Something evil is loose in London. The menacing figure of Edward Hyde stalks the streets, barging into women, trampling children, and even murdering an old man. But who is Hyde? And what is his relationship with the respectable doctor, Henry Jekyll? Part of the Usborne Reading Programme developed with reading experts at the University of Roehampton.